2000
DOI: 10.1016/s0022-5223(00)70129-2
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function after modified venovenous ultrafiltration in infants: A prospective, randomized trial

Abstract: Modified ultrafiltration produces an improvement in pulmonary compliance after bypass in infants. However, these improvements are not sustained past the immediate post-ultrafiltration period and do not lead to a decreased length of intubation or intensive care unit stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 13 publications
2
50
0
1
Order By: Relevance
“…This observation is common to most clinical series in both the pediatric 14,23 and the adult populations. 15,16 It is conceivable that standardized institutional policies on patient management may attenuate any discrepancy in outcome.…”
Section: I-256 Circulation September 18 2001mentioning
confidence: 76%
See 3 more Smart Citations
“…This observation is common to most clinical series in both the pediatric 14,23 and the adult populations. 15,16 It is conceivable that standardized institutional policies on patient management may attenuate any discrepancy in outcome.…”
Section: I-256 Circulation September 18 2001mentioning
confidence: 76%
“…15,16 Observations made in the pediatric population, including high-risk patients, have shown that ultrafiltration after cardiopulmonary bypass is associated with a mortality rate similar to the estimate for control patients. 7,9,11,12,14 Apparently, the severity of heart disease and the complexity of the operation have a more direct influence on operative mortality than bypass-related inflammatory reaction. The fact that the majority of early casualties in this study were due to untoward cardiac events would support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because MUF can eliminate excess water and ameliorate inflammatory reactions, it is unsurprising that the advantages of MUF on pulmonary function have been noted and widely accepted. In children, improvements of pulmonary function indexes including lung compliance, pulmonary vascular resistance, and oxygenation after ultrafiltration have been shown [7,13,14,31,41,48,49]. Nevertheless, a meta-analysis of RCT in pediatric patients failed to demonstrate the benefit of MUF on postoperative ventilation time.…”
Section: Effects Of Muf On Pulmonary Functionmentioning
confidence: 99%